Dioxygen activation and reduction by a soluble iron phthalocyanine - Iwanov, Christian; Hopp, Moritz Philipp; Lorenz, Domenik; Ballmann, Joachim; Enders, Markus (Chemistry - a European journal, 2023)
Iron ions in a square-planar coordination can bind molecules at the vacant axial positions and are able to transform them in stoichiometric and catalytic reactions. Nature takes advantage of these properties by incorporating iron into porphyrin systems, which play a key role not only in the binding and transport of oxygen, but also in catalytic oxidation and reduction reactions involving cytochrome P450. Although these systems have been studied extensively, there are still unresolved questions regarding the interplay between the iron ions and the surrounding ligands. Phthalocyanines (Pc) create a similar environment for metal atoms and FePc is known for a long time. However, without axial ligands FePc aggregates leading to solids of low solubility. In this work we used a known six-coordinate iron phthalocyanine derivative with bulky substituents and removed the stabilizing axial ligands. The resulting paramagnetic, four-coordinate compound does not aggregate and dissolves well so that NMR spectroscopy can be employed for studying the molecular structure and the reactivity. Solvent molecules bind weakly to the iron centers and oxygen is reduced in the presence of H-atom donors. The stoichiometric and catalytic reactivity with oxygen was studied in more detail.
Gesehen am 27.11.2023